2020
DOI: 10.3390/ma13040837
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Simulation to Study the Reduction of Welding Residual Stress by Ultrasonic Impact Treatment

Abstract: In this study, the effects of ultrasonic impact treatment (UIT) on the residual stress in a repair welding joint are investigated by experimental and finite element methods. A three-dimensional numerical analysis approach including a thermomechanical-coupled welding simulation and dynamic elastic-plastic UIT simulation is developed, which has been validated by X-ray diffraction measurement and indentation strain method. The results show that longitudinal residual stresses basically turned into the small tensil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Moreover, comparing Figure 6 b,e, it was clear that the stress at the welded joint was effectively eliminated after the aging treatment (the original stress of the AW joint was actually the residual tensile stress, which was not conducive to its service life). It can be seen from Figure 6 c,f) that certain stress was introduced into the fine grain and plastic deformation zones of the welded joint after DSUIT (the stress introduced here was residual compressive stress, which was beneficial to the service life of the welded component [ 27 ]). The fine grain zone displayed red (high) stress (i.e., residual compressive stress), and the residual compressive stress near the welded joint surface was too large, which led to the missing phenomenon in the EBSD analysis process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, comparing Figure 6 b,e, it was clear that the stress at the welded joint was effectively eliminated after the aging treatment (the original stress of the AW joint was actually the residual tensile stress, which was not conducive to its service life). It can be seen from Figure 6 c,f) that certain stress was introduced into the fine grain and plastic deformation zones of the welded joint after DSUIT (the stress introduced here was residual compressive stress, which was beneficial to the service life of the welded component [ 27 ]). The fine grain zone displayed red (high) stress (i.e., residual compressive stress), and the residual compressive stress near the welded joint surface was too large, which led to the missing phenomenon in the EBSD analysis process.…”
Section: Resultsmentioning
confidence: 99%
“…6 Cheng et al 7 measured the residual stresses induced by the UIT process using experimental measurement techniques and found that a compressive stress layer is generated. Chen et al 8 investigated the effects of UIT on the residual stress in a repair welding joint by experimental and finite element (FE) methods. The longitudinal residual stresses basically were reduced to small tensile stresses from large tensile stresses, and the transverse residual stresses mainly decreased to compressive stresses from large tensile stresses after UIT.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many scholars have studied the reduction in residual stresses in various types of mechanical components. The commonly used methods to eliminate residual stresses include stress relief heat treatment [25], vibration time effect method [26,27], ultrasonic impact method [28], pulse magnetization method [29,30], etc. However, these methods have limitations while removing stress, such as high energy consumption, a long cycle of stress relief heat treatment, it difficulty in controlling the deformation of components after stress relief.…”
Section: Introductionmentioning
confidence: 99%